Ugotavljanje vpliva stanovalcev na kakovost storitev v domu starejših občanov - Bukovec, Marija (Socialno delo, 2015)
The author presents the society, older people and demographic changes with projections which suggest that the population of older people will rise. The thesis outlines some stereotypes about older people and points to their stigmatisation, with special emphasis on social workers that should find answers for both - the label and stigmatisation. The second part of the article analyses interviews with residents who shared their experience according to our research questions regarding the course of their day, their influence on the services, the access to information, and the possibilities for personal development. The life of the interviewees is very monotonous, especially for immobile residents who daily face a dull routine. They are required to abide by the principles and house rules, therefore, they have verylittle influence on the life in the home for older people. The relations between the employees and the residents are not always respectful; the residents are often unable to influence the situation and have little privacy. As for the personal development, the residents are left to their own initiative.
Keywords: old age; starost; institucional care; institucionalno varstvo; autonomy; avtonomija; participacija; participation; personal development; osebnostni razvoj; social work; socialno delo